2013
DOI: 10.1093/mnras/stt1443
|View full text |Cite
|
Sign up to set email alerts
|

ULTRACAM z′-band detection of the secondary eclipse of WASP-12b

Abstract: We present z' -band secondary eclipse photometry of the highly irradiated hot Jupiter WASP-12b using ULTRACAM on the 4.2m William Herschel Telescope. We measure a decrease in flux of δ = 0.130 ± 0.013% during the passage of the planet behind the star, which is significantly deeper than the previous measurement at this wavelength (0.082 ± 0.015%, López-Morales et al. 2010). Our secondary eclipse is best fit with a mid-eclipse phase, φ, that is compatible with a circular orbit φ = 0.501 ± 0.002, in agreement wit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
30
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 46 publications
(89 reference statements)
3
30
2
Order By: Relevance
“…In this paper, we present two i -band secondary eclipse observations of WASP-12b that were conducted a year apart. The measured depths significantly disagree, mirroring the results of similar observations conducted at z -band wavelengths (López-Morales et al 2010;Föhring et al 2013). We also present an analysis of all reported WASP-12b secondary eclipse depths, in addition to a discussion of whether this could arise due to systematic errors or detectable variability in the WASP-12b dayside.…”
Section: Introductionsupporting
confidence: 74%
See 1 more Smart Citation
“…In this paper, we present two i -band secondary eclipse observations of WASP-12b that were conducted a year apart. The measured depths significantly disagree, mirroring the results of similar observations conducted at z -band wavelengths (López-Morales et al 2010;Föhring et al 2013). We also present an analysis of all reported WASP-12b secondary eclipse depths, in addition to a discussion of whether this could arise due to systematic errors or detectable variability in the WASP-12b dayside.…”
Section: Introductionsupporting
confidence: 74%
“…Madhusudhan (2012) predicted that for many hot Jupiters, thermal emission measurements at these wavelengths are good discriminators between carbonrich and carbon-poor exoplanets. Whilst secondary eclipse observations conducted at z -band wavelengths have been published for 9 exoplanets 1 (Sing & López-Morales 2009;López-Morales et al 2010;Smith et al 2011;Burton et al 2012;Gillon et al 2012;Lendl et al 2013;Zhou et al 2013;Föhring et al 2013;Chen et al 2014;Delrez et al 2016;Gaudi et al 2017;Delrez et al 2018), only two studies have reported secondary eclipse observations at i -band wavelengths (Mancini et al 2013;Chen et al 2014), with the most confident detection reported at 3.7σ.…”
Section: Introductionmentioning
confidence: 99%
“…While the host star is fairly faint (V = 12), WASP-12b's close semimajor axis and large radius (a = 0.0234 au, R R 1.90 Collins et al 2017) make it an excellent target for detailed study. Transit observations of WASP-12b range from 0.3 to 4.5μm, and eclipse observations range from 0.9 to 8.0μm (e.g., Hebb et al 2009;López-Morales et al 2010;Campo et al 2011;Madhusudhan et al 2011;Cowan et al 2012;Crossfield et al 2012;Copperwheat et al 2013;Föhring et al 2013;Sing et al 2013;Swain et al 2013;Stevenson et al 2014aStevenson et al , 2014bCroll et al 2015;Sing et al 2016). This work presents the first optical eclipse measurement of WASP-12b.…”
Section: Introductionmentioning
confidence: 92%
“…There have been extensive photometric and spectroscopic studies of WASP-12b (López-Morales et al 2010;Campo et al 2011;Chan et al 2011;Croll et al 2011;Husnoo et al 2011;Maciejewski et al 2011Maciejewski et al , 2013Madhusudhan et al 2011;Cowan et al 2012;Crossfield, Hansen & Barman 2012;Haswell et al 2012;Sada et al 2012;Sokov et al 2012;Southworth et al 2012b;Zhao et al 2012;Copperwheat et al 2013;Crossfield et al 2013;Föhring et al 2013;Fossati et al 2013;Mandell et al 2013;Sing et al 2013;Swain et al 2013;Bechter et al 2014 Table 14. Physical properties of WASP-12b, WASP-33b, WASP-36b, WASP-44b, WASP-48b, and WASP-77Ab derived from the light-curve modelling.…”
Section: Wasp-12bmentioning
confidence: 99%